Advances and Frontiers in Primate Seed Dispersal - Razafindratsima, Onja H.; Sato, Hiroki; Tsuji, Yamato; Culot, Laurence [UNESP] (Springer, 2018)
Primates play important roles as seed dispersers in many tropical ecosystems, such that studies of their seed dispersal services and impacts have gained interests among primatologists and ecologists in the past few decades. In this article, we first report that the number of scientific publications on primate seed dispersal has increased rapidly over the past 20years, based on an extensive literature review. These publications encompass diverse primate taxa from the four geographic regions where theynaturally occur. We then summarize the contributions to this Special Issue, which reflect on these progresses. Finally, we provide new directions for the next decade.
Keywords: Frugivore; Tropical forests; Pre-dispersal; Post-dispersal; Fruit removal; Seed fate